Guillain–Barré Syndrome Associated With Zika Virus Infection: A Prospective Case Series From Mexico - Soto-Hernández, José Luis; Ponce de León Rosales, Samuel; Vargas Cañas, Edwin Steven; Cárdenas, Graciela; Carrillo Loza, Karina; Díaz-Quiñonez, José Alberto; López-Martínez, Irma; Jiménez-Corona, María-Eugenia; Ruiz-Matus, Cuitláhuac; Kuri Morales, Pablo (Frontiers in Neurology, 2019)
Background: On May 2016, anticipating the rainy season from June to October in Mexico, we expected an increase in cases of Zika virus (ZIKV) infections. With the goal of identifying cases of GBS associated with ZIKV infection, a prospective joint study was conducted by a reference center for neurological patients and the Secretary of Health in Mexico City from July 2016 to November 2016. Methods: Serum, cerebrospinal fluid, urine, and saliva were tested by RT-PCR for ZIKV, dengue virus, and chikungunya virus in patients referred from states with reported transmissions of ZIKV infection, and with clinical symptoms of GBS according to the Brighton Collaboration criteria. Clinical, electrophysiological, and long-term disability data were collected. Results: In the year 2016 twenty-eight patients with GBS were diagnosed at our institute. In five hospitalized patients with GBS, RT-PCR was positive to ZIKV in any collected specimen. Dengue and chikungunya RT-PCR results were negative. All five patients had areflexic flaccid weakness, and cranial nerves affected in three. Electrophysiological patterns were demyelinating in two patients and axonal in three. Three patients were discharged improved in 10 days or less, and two patients required intensive care unit admission, and completely recovered during follow-up. Conclusion: Our results are similar to those reported from the state of Veracruz, Mexico, in which out of 33 samples of urine of patients with GBS two had a positive RT-PCR for ZIKV. Simultaneous processing of serum, CSF, urine, and saliva by RT-PCR may increase the success of diagnosis of GBS associated to ZIKV.